The effect of storage on the quality attributes of ultraviolet-irradiated and thermally pasteurised pineapple juices - Chia, Suet Lin; Shamsudin, Rosnah; Mohd Adzahan, Noranizan; Wan Daud, Wan Ramli (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The effect of storage time on the quality of ultraviolet-irradiated and thermally pasteurised pineapple juice was evaluated. The juices were irradiated with ultraviolet light (UV-C) at wavelength 254 nm (53.42 mJ/cm2, 4.918 s), thermally pasteurised at 800C for 10 minutes and stored at 40C for 13 weeks. There were significant changes in the total soluble solids, pH, titratable acidity and turbidity of UV-irradiated juice during storage, whereas for the same quality attributes of thermally pasteurised juice remained stable throughout the storage time. There were no significant changes in total phenolics for both treatments throughout the storage period. Other quality parameters (ascorbic acid, colour L, hue angle and chroma) were significantly affected by the storage time. Regarding the microbiological analysis, the total plate counts and yeast and mould counts of the UV-irradiated juice increased gradually throughout the 13 weeks of storage while these parameters remained unchanged in the thermally pasteurised juice with almost no microorganism growth. UV-irradiated pineapple juice preserved better quality attributes (TSS, pH, titratable acidity, ascorbic acid, turbidity, total phenolic, L (lightness), hue angle and chroma) than the thermal pasteurised juice during the storage time. Hence, UV irradiation has great potential as an alternative technology to thermal pasteurisation in producing products of high nutritive values.